Effect of Fatigue and Graded Running on Kinematics and Kinetics Parameters in Triathletes - Mateus, Greyce Any Sousa; Assumpção, Claudio Oliveira; Cabido, Christian Emmanuel Torres; Veneroso, Christiano Eduardo; Oliveira, Saulo Fernandes Melo; Fermino, Rogério César; Mortatti, Arnaldo; Lima, Leonardo Coelho Rabellode; Vilas Boas, Joao Paulo; Banja Fernandes, Túlio Luiz (International Journal of Sports Medicine, 2022)
This study aimed to evaluate the effect of cycling-induced fatigue on subsequent running with different ground inclinations on triathletes. Twenty male triathletes ran on a treadmill at individual speeds, on three inclines: level (0%), 7% uphill (7%), and 7% downhill (−7%). Subsequently, the athletes performed an incremental ramp-to-exhaustion (RTE) protocol on an ergometric bicycle until task failure and repeated the running protocol (POST-RTE). During running and cycling was monitored perceived exertion (RPE) and heart rate (HR). Plantar pressure distribution, peak plantar pressure, total foot area, and ground contact time were measured by an in-shoe sensor. Analysis of variance showed that HR (p=0.001; η2=0.63) and RPE (p=0.001; η2=0.82 large effect) were higher in POST-RTE, without interactions between slopes and fatigue. The heel load showed difference between 0 and 7% and 7 and −7% (p=0.001; η2=0.44 large effect) with higher value in −7%. The midfoot showed differences between 0 and −7% with higher value in 0% (p=0.03; η2=0.15 small effect). The contact time showed interactions between fatigue and slopes with a higher value in POST-RTE. Coaches should be aware that training on the uphill and downhill surfaces can alter the plantar load on different foot parts.
Keywords: plantar load; uphill running; downhill running